OPINIONS OF TEACHERS ABOUT PRESIDENCY OF RELIGIOUS AFFAIRS, CEM HOUSES, ALEVISM (THE CASE OF ELAZIĞ SAMPLE) - Şuayip ÖZDEMİR (Fırat University, 2019)
In this study is used survey data with teachers that associated with the idea of Alevi-Bektashi that reside in the center of Elazig province from survey data that aimed to determine various aspects of the views of Alevi-Bektashis about Presidency of Religious Affairs. In the study, “ascribed meaning to Alevism”, “sources of informations were acquired related to Alevism”, “the frequency of reading books related to Alevism”, “the situation of the Cem Houses”, “the Cem Houses’ being supported by the state,”, “their being represented in Department of Religious Affairs”, “that religious service should give to Alevis by Department of Religious Affairs”, “informing about Alevism to religious officials”, “Alevis’ need to religious officials in the religious issues”, directed questions on these ıssues, we tried to search out the opinions of teachers of belonging to the idea of Alevis-Bektashi. Important results that is obtained in the study, teachers that belonging to the idea of Alevi-Bektashi that they receive from their families informations on Alevism, that they see Alevism as a culture, cult, a way of thinking, a different interpretation of Islam and sect, that they see cem houses as a place of worship and culture, that they want to be supported by the state of cem houses, that they look on positively that Alevis’ are represented the Presidency of Religious Affairs, that they agree that is developed the knowledges of religious officers in areas inhabited by Alevis, that they be of opinion that give place to publications on Alevism by Presidency of Religious Affairs, that they need to religious officers in transferring religious informations to children, the funeral operations, the reading of Prophet's Birthday, the Qur'an reading, religious marriages. It has been proposed that make the necessary arrangements in this context, to deal with the problems of religious of the Alevis, to care about their views and to be in contact with leaders of Alevis and Chairmen of Alevi foundations and associations of Presidency of Religious Affairs in this study.